Fabrication of organic light-emitting devices comprising stacked light-emitting units by solution-based processes - Pu, Yong-Jin (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.